Sonodynamic Excitation of Rose Bengal for Eradication of Gram-Positive and Gram-Negative Bacteria. (19th December 2012) - Nakonechny, Faina; Nisnevitch, Michael; Nitzan, Yeshayahu; Nisnevitch, Marina
Abstract : Photodynamic antimicrobial chemotherapy based on photosensitizers activated by illumination is limited by poor penetration of visible light through skin and tissues. In order to overcome this problem, Rose Bengal was excited in the dark by 28 kHz ultrasound and was applied for inactivation of bacteria. It is demonstrated, for the first time, that the sonodynamic technique is effective for eradication of Gram-positive Staphylococcus aureus and Gram-negative Escherichia coli . The net sonodynamic effect was calculated as a 3-4 log10 reduction in bacteria concentration, depending on the cell and the Rose Bengal concentration and the treatment time. Sonodynamic treatment may become a novel and effective form of antimicrobial therapy and can be used for low-temperature sterilization of medical instruments and surgical accessories.